Edukasi Gema Cermat golongan obat keras pada guru dan orang tua siswa SDN 11 Pangkalan Baru, Bangka Tengah - Lana Sari; Mirnawati Zalili Sailan; Dela Lanaya (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
A pharmacist is a profession that can optimize pharmaceutical services for the community. As part of health workers and the front line for drug distribution to the community, pharmacists must contribute significantly to socializing Gema Cermat, especially for prescription drugs that are often purchased without a doctor's prescription. Pharmacies can only submit prescription drugs based on a doctor's prescription. This provision aims to prevent the illegal use or drug means of this group. The phenomenon of irregularity in the circulation of hard drugs in prescription drug services without a prescription in pharmacies cannot be separate from the community itself. The tendency of people who want to do self-medication encourages the rampant phenomenon of deviance. This activity aims to see an increase in knowledge of the prescription drugs class through Gema Cermat education for teachers and parents of SDN 11 Pangkalan Baru, Central Bangka Regency. The activity was carried out in the classroom at SDN 11 Pangkalan Baru, carried out through a pre-test and post-test using a questionnaire. The results obtained showed that the knowledge of the participants was 62.50%. There is a significant difference with a value of 0.000, which means an increase in understanding parents' and teachers' knowledge before and after Gema Cermat education about prescription drugs.